Towards Life Cycle Perspective in Activities of Small and Medium Enterprises in Poland - Jolanta BARAN (Communications of International Proceedings, 2020)
The growing needs of enterprises in the integration of environmental life cycle aspects into product development, related to the implementation of new legal regulations, result in the searching the relevant tools to meet these needs. The aim of this study is to present the conditionings for the inclusion of the life cycle perspective in activities undertaken by SMEs, as well as to analyze possible barriers and eco-design procedures in terms of its application by small and medium-sized enterprises.
Keywords: Small And Medium Sized Enterprises; Life Cycle Assessment; Ecodesign; Environmental Aspects